Future options of electricity generation for sustainable development: Trends and prospects - Fazlur Rashid; Mohammad U. H. Joardder (Engineering Reports, 2022)
Abstract Electricity is an important part of our daily life. It is mainly generated from conventional energy sources. Conventional energy sources are diminishing day by day; whereas, energy demand increases significantly. Moreover, less land availability, low budget for energy, and weather‐dependent renewable sources result in poor energy management all over the world. Therefore, proper management of conventional energy and simultaneous finding of potential alternative energy sources are the prime concerns of energy‐related researchers. In this article, literature relating to less‐implemented energy sources is reviewed to demonstrate their current status and future prospects. This review shows that along with current renewable and conventional sources of energy, these less‐implemented energy sources can contribute substantially to overcome the energy scarcity in electricity production. Proper planning and improvement are required to get sufficient benefits from these less‐implement energy sources. In order to clarify the electricity generation from less‐applied energy sources, many figures are adapted using the concept and information of reviewed literature. In those figures and related text, several possible ways of electricity generation using these energy sources and their potential implementation techniques with related challenges have been outlined. The electricity generation rate and their corresponding applications are also depicted. Proper steps to popularize these less‐focused sources of energy would mitigate high energy demand all over the world and offers a cleaner environment for livelihood.